Teoria e prática da gestão democrática na escola pública: um estudo com egressos de um curso de pós-graduação lato sensu da universidade estadual do Ceará - Oliveira, Rômulo Vieira de (2020)
In this research, we aim to investigate the relationship between the concepts of democratic school management and their effective applicability in the daily lives of ex-students of the lato sensu graduate program on the school management course at State University of Ceará - UECE. Its specific objectives are: a) to analyze concepts and assumptions about democracy in the light of theoretical and historical elements; b) to examine contextual elements of contemporary capitalism that reverberate over the basic school management; c) to discuss how the democratic management concepts influence the day-to-day life of teachers in management positions; d) to analyze factors that facilitate or hinder the democratic management practice in the managers daily routine. From records of school premises experiences, we observe the subjective appropriations in the way of thinking and acting of different historical subjects and we outline a profile of how democratic management is practiced and what are the problems that prevent this model from being able to be applied in its essence. With regard to methodological procedures, a qualitative nature research constitutes a bibliographic documentary and field study, organized from the theoretical framework critical to the current aegis of public policies that link to capital. In this sense, we work with the concept of democracy throughout the historical formation of humanity, addressing classic, liberal and Marxist precepts. In addition, we took a theoretical approach to the emergence and deepening of democratic school management concept in Brazil and the different school management concepts. Finally, results show that democratic management has undergone remarkable advances in legal terms, but it still lacks a materialization that brings effective participation by teachers, parents and students in the construction of a quality public school. In addition, we perceive management in the school environment as another instrument for reproducing mechanisms of the capitalist order.